Primary liposarcoma of the ascending colon: a rare case of mixed type presenting as hemoperitoneum combined with other type of retroperitoneal liposarcoma - Choi, Yoon Young (BioMed Central, 2010)
BACKGROUND: Liposarcoma occurs most commonly in the extremities and retroperitoneum, however, it has been rarely observed in the colon. CASE PRESENTATION: A case is reported a 41-year-old man with liposarcoma of ascending colon which was presented as hemoperitoneum and combined with a different histological type of retroperitoneal liposarcoma. He visited hospital with right lower abdominal pain and palpable mass. Laboratory data including tumor markers were within normal limits, and computed tomography revealed a 15 × 10 cm sized enhancing soft mass. Right hemicolectomy was performed, and after that, a further large retroperitoneal mass was revealed and this was also radically excised. Mixed-type colon liposarcoma and well differentiated type of retroperitoneal liposarcoma were diagnosed in pathologic report. The patient has remained free of disease for 24 months. CONCLUSIONS: No standardized guidelines have been established for its treatment because too small a number of cases have been reported, but surgical resection was considered the treatment of choice.